Six Cases of Polypoidal Choroidal Vasculopathy in Eyes with Choroidal Nevi - Andrea Gaggino; Leandro Inferrera; Serena Milan; Marianna Presotto; Daniele Tognetto (Case Reports in Ophthalmology)
Introduction: The aim of this study was to report the cases of 6 patients with the coexistence of polypoidal choroidal vasculopathy (PCV) and choroidal nevi. Case Presentation: Six patients with the coexistence of PCV and choroidal nevi were thoroughly evaluated by slit-lamp biomicroscopy examination, color fundus photography, optical coherence tomography (OCT), OCT angiography (OCT-A), fluorescein angiography (FA), indocyanine green angiography (ICG-A), fundus blue autofluorescence (BAF), and ocular ultrasound (OU). The typical features of PCV and nevi were present in all patients, three of whom were treated with intravitreal anti-angiogenic agents. In each clinical case, the choroidal Haller’s vessels adjacent to the nevus were visibly more dilated compared to normal. Color fundus photography, OCT, OCT-A, FA, ICG-A, BAF, and OU revealed similar findings across all cases. Observations revealed that choroidal nevi could instigate modifications in the outer retina, resulting in persistent alterations capable of triggering the formation of neovascularization. Conclusion: The occurrence of a PCV alongside nevus is an uncommon complication. Findings from all exams performed were consistent across all cases, highlighting the potential link between PCV and nevi.